Cannabidiol Enhances the Therapeutic Efficacy of Olsalazine and Cyclosporine in a Murine Model of Colitis - Thapa, Dinesh; Patil, Mohan; Warne, Leon N.; Carlessi, Rodrigo; Falasca, Marco (International journal of molecular sciences, 2025)
Current therapies for inflammatory bowel disease (IBD), such as olsalazine and cyclosporine, often exhibit limited long-term efficacy and are associated with adverse effects. Cannabidiol (CBD), a non-psychoactive phytocannabinoid, shows promise for its anti-inflammatory properties, though its effectiveness as a monotherapy remains inconclusive. This study investigates the therapeutic potential of combining low-dose CBD (10 mg/kg) with olsalazine (50 mg/kg) or cyclosporine (2.5, 5 mg/kg) in dextran sulphate sodium (DSS)-induced acute and chronic colitis models in mice. Disease severity was assessed via disease activity index (DAI), colon morphology, cytokine and chemokine expression, myeloperoxidase (MPO) activity, systemic inflammatory markers, and glucagon-like peptide-1 (GLP-1) regulation. Safety evaluations included haematology and plasma biochemistry. DSS-treated mice showed elevated DAI scores, colon shortening, heightened inflammation, and organ enlargement. Combination therapies significantly ameliorated colitis, reducing DAI, MPO activity, and inflammatory cytokines, while restoring colon length and GLP-1 levels—without inducing liver or kidney toxicity. These findings demonstrate that combining a low dose of CBD with standard IBD drugs enhances therapeutic efficacy while minimizing side effects, supporting its integration into future combination strategies for more effective and safer IBD management.